2017
DOI: 10.1111/fcre.12291
|View full text |Cite
|
Sign up to set email alerts
|

Young Children in Divorce and Separation: Pilot Study of a Mediation‐Based Co‐Parenting Intervention

Abstract: This article reports on a cluster randomized pilot study of a mediation‐based intervention for separated parents of very young children, Young Children in Divorce and Separation (YCIDS). The control group intervention was “Mediation plus Reading.” Participants were separated parents attending mediation over a co‐parenting dispute concerning a child under the age of 5 years (n=33 cases). Nine of the 16 key child and parent outcomes were significantly better for the intervention group, with the remainder nonsign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The majority of divorce-related intervention programs have focused on children, divorce conflict, and co-parenting skills as the outcomes (Boring et al, 2015;Greenberg et al, 2019;Klein Velderman et al, 2018;McIntosh & Tan, 2017;Pelleboer-Gunnink et al, 2015;Sandler et al, 2018). Those that have targeted adults typically focus on depression or post-divorce adjustment as the outcomes in intervention assessment (e.g.…”
Section: Palabras Clavementioning
confidence: 99%
“…The majority of divorce-related intervention programs have focused on children, divorce conflict, and co-parenting skills as the outcomes (Boring et al, 2015;Greenberg et al, 2019;Klein Velderman et al, 2018;McIntosh & Tan, 2017;Pelleboer-Gunnink et al, 2015;Sandler et al, 2018). Those that have targeted adults typically focus on depression or post-divorce adjustment as the outcomes in intervention assessment (e.g.…”
Section: Palabras Clavementioning
confidence: 99%
“…On the contrary, our findings support the social imperative to give increasing attention and resources to the support of mothers who have experienced IPV, in safeguarding attachment security in their children, and de-escalating the negative impact of IPV on developmental pathways. This may include new psychoeducational approaches to enhancing parent awareness of the associations that IPV exposure may have with the development of their child’s attachments (McIntosh, 2015; McIntosh & Tan, 2017) as well as implementing attachment-based parenting interventions in cases where IPV has been identified (Lieberman, Chu, Van Horn, & Harris, 2011). Given the strong intergenerational transmission of IPV risk, doing so may improve the social–emotional health of generations to come.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Australia, researchers report that there were risks to children's healthy development in some parenting arrangements when parents display particular characteristics. Children, under the age of 10 and in high‐conflict parenting situations, were least satisfied with shared parenting arrangements while children under the age of four reflected negative impacts from shared parenting arrangements, such as higher irritability and distressed parent–child interactions (McIntosh & Chisholm, 2008; McIntosh et al, 2010; Trinder, 2010). In the United States, two quantitative studies reported similar negative outcomes for children in situations of domestic violence including short and long‐term emotional and developmental outcomes (Udo et al, 2016) and neurological impacts (Easterbrooks et al, 2018).…”
Section: Context Of Domestic Violence In Parenting Plan Arrangementsmentioning
confidence: 99%